The Anthem Companion to Auguste Comte - Wernick, Andrew (Anthem Press, 2017)
For most of the twentieth century, Auguste Comte, a controversial but highly influential nineteenth-century figure, and his vast treatises on positive philosophy, politics and religion were disregarded and largely ignored. More recently, however, Comte's life and writings have been reexamined together with the project of social reform to which his intellectual labors were devoted, producing a much more complicated picture of his thought and its significance. The Anthem Companion to Auguste Comte-with ten new critical essays by leading Comte scholars, sociologists, intellectual historians, social theorists and philosophers-aims to further this reexamination while also providing a multifaceted introduction to Comte's thought and to current discussion about him. The essays also examine Comte's relation to a multiplicity of other thinkers, and his place more generally in the formation and legacy of modern Western thought.